Selection of Non-Saccharomyces Yeasts from Extreme Oenological Environments for Potential Use in Winemaking - María Trinidad Alcalá-Jiménez; Juan Carlos García-García; Juan Carlos Mauricio; Juan Moreno; Rafael Peinado; Teresa García-Martínez (Microorganisms)
This study evaluated the oenological potential of two non-Saccharomyces yeast strains, Hanseniaspora opuntiae TR-5 and Zygosaccharomyces bailii L-25, isolated from extreme winemaking environments in southern Spain. Out of 156 yeast isolates screened from high-sugar musts and flor yeast biofilms, strains were selected based on their β-glucosidase activity, killer phenotype, and ethanol production, traits associated with aroma release and microbial competition. Fermentation trials on sugar-rich synthetic medium showed that both H. opuntiae and Z. bailii achieved ethanol yields of 10% v/v and residual sugars at 4 g/L. Co-culture and sequential inoculation, with H. opuntiae introduced first and Z. bailii added on day four, resulted in complete alcoholic fermentation and a reduction in undesirable acetoin levels compared to single-strain fermentations. These findings highlight the practical potential of using selected non-Saccharomyces strains in sequential fermentations to improve aroma complexity, fermentation reliability, and sensory quality in wines, even in the absence of Saccharomyces cerevisiae. The application of these strains offers a novel approach for precision oenology and varietal expression in challenging musts.